Treatment of crude oil contaminated sand:porosity and permeability study: article - Amad Nizamuddin, Nur Amanina; Mat Shayuti, Muhammad Syafiq (2018)
Sand production remains as major issues in oil and gas industry. Current sand management in oil and gas is involved transportation onshore that is costly, time consume and required high amount of manpower. Improvement of this sand handling techniques such as treat and disposal sand offshore requires detail information of contaminated sand properties. Previous studies focused more on geotechnical properties of crude oil-contaminated sand but not in its chemical properties. This research of studies was undergone to gather more information on crude oil-contaminated sand characterization details on the porosity, permeability and chemical composition. For porosity, real sand sample has porosity of 67.1% and model sand sample has porosity of 46.6% calculated by lab manual calculation and later on, proved by observation on FESEM. Constant head sand pack permeability test was used to determine permeability of sand samples. Real sand sample value of coefficient, k=0.23 with deionized water, and k=0.14 with brine. Model sand sample value of coefficient, k=2.04 with deionized water and k=1.92 with brine. FTIR were used to identify compositions of real sand sample, model sand sample and contaminant. Sand samples consist of quartz, feldspar, clay and carbonate while contaminant has aromatic, alkane and ester. The composition of sand was rechecked by using EDX that was assembled to FESEM.